1992
DOI: 10.1111/j.1469-8137.1992.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of ozone stress and resulting status of ribulose bisphosphate carboxylase/oxygenase and associated net photosynthesis

Abstract: Experiments were conducted to determine how the timing of an exposure to ozone influenced the impact of the gas on ribulose-l,5-bisphosphate carboxylase/oxygenase (Rubisco) throughout the life span of a designated leaf. Saplings of Populus maximowizti x trichocarpa XE 388 received 5-d exposures to O^ in growth chambers during and at the termination of presumed synthesis of Rubisco in a designated leaf. Ozone had no detectable impact on Rubisco activity or quantity when the exposure occurred during the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
96
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(109 citation statements)
references
References 22 publications
13
96
0
Order By: Relevance
“…Similarly, co.-occurring reductions in photochemical and photosynthetic processes were reported for Pinus taeda L. seedlings in response to three seasons of fumigation with 92 ppb ozone (Sasek & Richardson, 1989). Pell, Eckardt & Enyedi (1992) observed a direct effect of ozone on the COj-fixing capabilities of Populus maximowizii X trichocarpa leaves.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, co.-occurring reductions in photochemical and photosynthetic processes were reported for Pinus taeda L. seedlings in response to three seasons of fumigation with 92 ppb ozone (Sasek & Richardson, 1989). Pell, Eckardt & Enyedi (1992) observed a direct effect of ozone on the COj-fixing capabilities of Populus maximowizii X trichocarpa leaves.…”
Section: Discussionmentioning
confidence: 97%
“…Reduced leaf biomass may be a result of disturbed photosynthesis and declined production, these being well known responses to ozone stress (e.g. Darrall, 1989;Matyssek et al, 1991;Pell et al, 1992), Ozone has been reported to cause a wide array of visible symptoms depending on the type and variety of plant, the concentration and duration of O3 exposure, and other interacting factors (Krupa & Manning, 1988). In birch, Matyssek e« a/.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone effects on stomatal conductance were insignificant in the spring (data not shown). In the autumn Cherry Belle exhibited an 03-induced reduction in stomatal conductance as previously reported (Pell et aL, 1992). Both genotypes exhibited similar conductance rates within and across seasons so only results for Cherry Belle are illustrated.…”
Section: Environmental Parametersmentioning
confidence: 57%
“…Leaf conductance was determined five times during each experiment by methods previously described (Pell, Eckardt & Enyedi, 1992). Measurements were determined for the oldest leaf on the plant and were followed throughout the maturing process.…”
Section: Analysis Of Plantsmentioning
confidence: 99%